2012
DOI: 10.1016/j.livsci.2012.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vitro and in vivo fertilizing potential of bovine semen frozen in egg yolk or new lecithin based extenders

Abstract: a b s t r a c tOne of the main factors known to influence quality and fertility of bovine cryopreserved semen is the extender used. In this matter, a great worldwide interest has been directed to the development of chemically defined media, free of animal origin products. The objective of the present study was to compare the efficacy of three bovine semen extenders: Tris-fructose (TRIS, control with 20% egg yolk), Botu-Bov s (BB; 20% egg yolk), and Botu-Bov s -soy lecithin (BB-L; 1% soy lecithin). Towards this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 24 publications
3
58
1
3
Order By: Relevance
“…The improvement of kinetic motilities in these studies was attributed to the anti-oxidant activities of their additives, by improving the membrane fluidity of sperm and resistance against freezing-thawing shock (Kaka et al, 2015b). In an earlier study that was established by Crespilho et al (2012), it was found that lecithin based diluent did not differ much with tris-based egg yolk diluent in terms of sperm's kinetic motilities of frozen bull semen in exception of STR and LIN, the high value of these two parameters was attributed to low viscosity of lecithin based diluent as compared to other diluents such as tris-based egg yolk and skim milk diluents (Thun et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of kinetic motilities in these studies was attributed to the anti-oxidant activities of their additives, by improving the membrane fluidity of sperm and resistance against freezing-thawing shock (Kaka et al, 2015b). In an earlier study that was established by Crespilho et al (2012), it was found that lecithin based diluent did not differ much with tris-based egg yolk diluent in terms of sperm's kinetic motilities of frozen bull semen in exception of STR and LIN, the high value of these two parameters was attributed to low viscosity of lecithin based diluent as compared to other diluents such as tris-based egg yolk and skim milk diluents (Thun et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The lipid particles found in most extenders could play a deleterious role on sperm movement trajectory evaluated by CASA (CRESPILHO et al, 2012) and possibly in sperm concentration determined by the same method. Because of this, in the present study we did not consider bull sperm samples cryopreserved in milk extenders for the concentration evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…The steps of producing insemination doses (diluting the sperm, filling the straws, cooling and freezing) have a significant effect on sperm motility after thawing (Siddique et al 2006). Especially, the properties of extender used (Crespilho et al 2012;Cao et al 2013;Špaleková et al 2014) and freezing methods are important (Watson 2000;Medeiros et al 2002).…”
Section: Reproduction Bull Sperm Extender Ldl Cholesterol Sperm Smentioning
confidence: 99%